Penerapan Model Permainan (Games) dalam Pembelajaran Bahasa Indonesia di Kelas V Sekolah Dasar (Studi Literatur) - Ade Dina Nurkhakiki; Dewi Nopasari (Action Research Journal, 2025)
Game-based learning models in elementary schools have great potential to improve student learning outcomes. This approach not only facilitates better understanding of the material but also motivates students to be significant. This study aims to investigate the effectiveness of game-based learning models in improving student learning outcomes in elementary schools, especially in the context of Indonesian language learning. This study uses a literature study method by collecting secondary data in the form of previous research results that apply game-based learning models. The data analysis method used is content analysis to explore the effectiveness of various game learning models. The results of the study indicate that the application of game learning models such as ESTASI in poetry learning and Teams Games Tournament in thematic learning can significantly improve students' writing skills and their learning outcomes. For example, students involved in the ESTASI game showed increased creativity and participation in writing poetry, while students who participated in the Teams Games Tournament showed increased activity and achievement of learning outcomes. The integration of game learning models in elementary school education promises positive and sustainable results for students' academic development. This approach not only improves students' understanding and skills but also helps maintain their learning motivation. The implication of this research is the importance of implementing varied and interesting learning models to create an effective and enjoyable learning environment for students at the elementary level